Genetic diversity of Striga hermonthica (Del.) benth. weeds from Nigeria and Kenya, and the genetic responses of selected hist maize lines - Unachukwu, N.N. (University of Ibadan, 2019)
Striga hermonthica (SH) is a parasitic weed that attacks and significantly reduces the yield of maize in Africa. The genetic interactions responsible for resistance or susceptibility of hosts to the parasite and the genetic differentiation that exists between and within SH populations are not fully known. This study investigated the genetic diversity of SH populations in the largest maize producers in Sub-Saharan Africa (Kenya and Nigeria) and; the genetic responses of a susceptible (5057) and a resistant (ZD05) maize genotype to SH infestation. The SH plants were collected from farms across western Kenya (KSH) and northern Nigeria (NSH) in October 2012 and authenticated at the Department of Botany, University of Ibadan (UIH-22774). The plants (n=1029) were then genotyped with 1576 single nucleotide polymorphism markers and indices of genetic diversity [effective alleles (Ne), Shannon’s information index (I), expected (He) and observed heterozygosity (Ho)] were determined. Population structure and fixation index (Fst), were assessed to identify genetic differentiation between and within KSH and NSH populations. Two maize varieties (5057 and ZD05) were divided into four groups of nine plants each and planted in rhizotrons (root observation chambers). Seven days after planting, three groups of each maize genotype were infested with pre-germinated SH and the fourth was used as uninfested control. Root tissue was taken at 3, 9 and 22 days post infestation (DPI) and total ribonucleic acid ( ribonucleic acid ( ribonucleic acid (ribonucleic acid (ribonucleic acid (ribonucleic acid ( ribonucleic acid (RNA) was extracted using standard method. The root transcriptome was sequenced using next-generation sequencing. Gene expression levels of secondary metabolism, of secondary metabolism, of secondary metabolism, of secondary metabolism, of secondary metabolism, of secondary metabolism, of secondary metabolism, of secondary metabolism, defence defence defence defence, and , and , and antiapoptotic genes antiapoptotic genes antiapoptotic genes antiapoptotic genes antiapoptotic genes antiapoptotic genes antiapoptotic genes antiapoptotic genes were determined by profiling the messenger RNA levels and determined by profiling the messenger RNA levels and determined by profiling the messenger RNA levels and determined by profiling the messenger RNA levels and determined by profiling the messenger RNA levels and determined by profiling the messenger RNA levels and determined by profiling the messenger RNA levels and determined by profiling the messenger RNA levels and determined by profiling the messenger RNA levels and determined by profiling the messenger RNA levels and determined by profiling the messenger RNA levels and determined by profiling the messenger RNA levels and determined by profiling the messenger RNA levels and determined by profiling the messenger RNA levels and determined by profiling the messenger RNA levels and determined by profiling the messenger RNA levels and determined by profiling the messenger RNA levels and determined by profiling the messenger RNA levels and determined by profiling the messenger RNA levels and determined by profiling the messenger RNA levels and determined by profiling the messenger RNA levels and determined by profiling the messenger RNA levels and determined by profiling the messenger RNA levels and comparing the logcomparing the log comparing the log comparing the log comparing the log 2 fold-change (LFC) between the infested and uninfested maize plants and between the genotypes. Data were analysed using two-way ANOVA at α0.05. The two populations of SH displayed high levels of genetic diversity. KSH showed higher levels (Ne=1.41±0.01, I=0.38±0.01, Ho=0.28, He=0.25±0.0) than NSH (Ne=1.41±0.01, I=0.332±0.01, Ho=0.21, He=0.20±0.00). Significant genetic differentiation (Fst=0.15) was observed between the two populations and between three subpopulations detected within the NSH population (Fst =0.053). At 3DPI, secondary metabolism and defence genes, benzoxazineless 1 (LFC=2.5) and chalcone synthase 2 (LFC=3.2), were upregulated in ZD05, while in 5057, antiapoptotic genes, bax inhibitor1 (LFC=1.4) and bcl-2 binding anthanogene-1 (LFC=1.7) were upregulated. At 9DPI, secondary metabolism and defence genes, chalcone synthase (LFC=-1.7) and cellulose synthase (LFC=-1.7), were downregulated in 5057, while secondary metabolism and defence genes, chalcone isomerase (LFC=2.3), cellulose synthase (LFC=1.5), chitinase (LFC=1.6) and phenylalanine ammonia-lyase1 (LFC=1.8) were upregulated in ZD05. At 22 DPI, secondary metabolism and defence genes, chalcone synthase (LFC=-2.9) and phenylalanine ammonia-lyase1 (LFC=-2.9), were down regulated in 5057, while in ZD05, secondary metabolism and defence genes, bx13 (LFC=1.8), chalcone synthase (LFC=1.8), phenylalanine ammonia-lyase (LFC=2.6) and antiapoptotic gene, bax inhibitor1 (LFC=1.8) were upregulated. Striga hermonthica populations in Kenya and Nigeria are genetically distinct and ecotypes exist within Nigeria. Genes involved in secondary metabolism and defence were upregulated in the resistant maize genotype, but down regulated in the susceptible genotype. The resistant line mobilized a more comprehensive response to the parasite than the susceptible line.